Detoxification and decolorization of complex textile effluent in an enzyme membrane reactor: batch and continuous studies - Dahiya, Manju; Islam, Dar Tafazul; Srivastava, Preeti; Sreekrishnan, T. R.; Mishra, Saroj (Frontiers in Microbiology, 2023)
There is an urgent need to look for bio-based technologies to address the pollution related to textile dyes in waterbodies. The aim of this study was to evaluate an engineered laccase variant, LCC1-62 of Cyathus bulleri, expressed in recombinant Pichia pastoris, for decolorization and detoxification of real textile effluent. The partially purified laccase effectively ( 60-100%) decolorized combined effluent from different dyeing units at a laccase concentration of 500 U/L at a 50 mL level. Decolorization and detoxification of the combined effluents, from a local textile mill, were evaluated at 0.3 L volumetric level in a ray-flow membrane reactor in batch and continuous mode of operation. In batch studies, maximum decolorization of 97% and detoxification of 96% occurred at a hydraulic retention time (HRT) of 6 h without any additional laccase requirement. In continuous studies, the reactor was operated at an HRT of 6 h with a lower enzyme dosage ( 120 U/L of the effluent). Decolorization was accompanied by a loss in laccase activity which was restored to 120 U/L by the addition of laccase in two regimes. The addition of laccase, when the residual laccase activity dropped to 40% ( 50 U/L), resulted in high decolorization ( 5 ppm residual dye concentration) and low variance (σ2) of 2.77 while laccase addition, when the residual dye concentration dropped to 8% ( 10 U/L), resulted in average dye concentration of 13 ppm with a high variance of 62.08. The first regime was implemented and the continuous reactor operated for over 80 h at an HRT of 3 and 6 h, with the latter resulting in 95% decolorization and 96% reduction in the mutagenicity of the effluent. Less than 10% membrane fouling was observed over long operations of the reactor. The findings strongly suggest the feasibility of using LCC1-62 in an enzyme membrane reactor for large-scale treatment of textile effluents.